High temperature mechanical behavior of plasma-nitrided inconel 625 superalloy - Oliveira, M. M.; Couto, A. A.; Baldan, R. [UNESP]; Reis, D. A.P.; Vatavuk, J.; Vendramim, J. C.; Lima, N. B.; Reis, A. G. (Springer Nature, 2017)
INCONEL 625 nickel-based superalloys present limitations for use at temperatures above 600 °C. For this reason, protective coatings can be used as barriers to avoid both nucleation and crack propagation. The aim of this work is to evaluate the mechanical properties at high temperatures of non-nitrided and plasma-nitrided samples of the INCONEL 625 superalloy. The microstructural characterization of the nitrided layer was performed with the aid of optical microscopy (OM) and X-ray diffraction (XRD). Tensile tests were performed between 600 and 1000 °C and deformation rates between 0.0002 and 0.002 s−1. The results have shown that nitrided sample present expanded fcc phase and chromium nitride (CrN) phases. Tensile tests showed that there was no significant difference in the yield strength and elongation between non-nitrided and plasma-nitrided samples at the same temperatures. Serrated stress–strain behavior was observed in the curves obtained at 600 and 700 °C, which was associated with the dynamic strain aging effect. At 600 °C, the increase in strain rate promoted an increase of the amplitude and oscillation frequency of the stress.
Keywords: Inconel 625; Mechanical properties; Plasma-nitriding; Superalloys